From palimpsest to me-moiré: Exploring urban memorial landscapes of political violence. (October 2019) - Pirker, Peter; Rode, Philipp; Lichtenwagner, Mathias
Abstract: This paper presents a model for exploring urban memorial landscapes on political violence. It is based on a survey of more than 1, 600 memorials erected in public spaces of the Austrian capital, Vienna, since 1945 with references to the Austrofascist and the National Socialist regimes. The paper builds on existing theoretical and methodological concepts, such as the 'social production of space' (Von Seggern & Werner, Löw), the 'socio-spatial condition of commemoration' (Dwyer & Alderman), 'symbolic accretion' (Dwyer) and 'figurations of memory' (Olick), and submits them to quantitative analysis using descriptive statistics and mapping. In order to distinguish between temporal and spatial patterns of memorialization, the paper explores all memorials along a range of spatial, temporal, thematic and social subjects and then identifies 'layers of memorialization', which express the structure under which mnemonic actors at specific times and under specific political conditions have addressed and negotiated specific issues of political violence worth of memorialization. After an analytical disentanglement, the paper presents a recomposed map of the urban memorial landscape by overlaying the main spatial-temporal clusters of six layers of memorialization. Instead of applying the widely used term of 'palimpsest', the paper suggests the notion of 'me-moiré' for grasping the historically and spatially structured coexistence of diverse temporalities, issues and social and political dimensions present in the urban memorial landscape on political violence.